"Tai Chi" philosophy driven rigid-flexible hybrid ionogel electrolyte for high-performance lithium battery. (May 2018) - Chen, Nan; Xing, Yi; Wang, Lili; Liu, Fan; Li, Li; Chen, Renjie; Wu, Feng; Guo, Shaojun
Abstract: Dendritic growth of Li metal and its related safety issue in a liquid electrolyte greatly hinder the development of Li metal batteries. Herein, inspired by the Tai Chi philosophy of keeping rigid and flexible balance, we demonstrate a new rigid-flexible hybrid ionogel electrolyte composed of TiO2 rigid framework, PVDF-HFP flexible framework and LiTFSI-Py13TFSI ionic liquid for greatly boosting the performance of Li battery. The as-made hybrid ionogel electrolyte not only has excellent electrochemical properties, such as ionic conductivity up to 7.4 × 10 −3 S/cm at 25 °C and anodic stability up to 5.5 V versus Li/Li +, but also has a high mechanical strength to withstand extrusion. These important features make it be able to realize the stable stripping/plating of Li anodes. The hybrid ionogel electrolyte enables the assembled LiFePO4 /Li batteries to be successfully cycled at wide C rate (0.1–2.0 C) and exhibit no significant capacity degradation for up to 500 days (about 600 cycles) at a 0.1 C rate. The design from Tai Chi philosophy to protect Li metal opens new opportunities to realize high energy-density Li metal batteries. Graphical abstract: Rigid-flexible hybrid ionogel electrolytes derived from Tai Chi philosophy are fabricated as quasi-solid electrolytes for boosting the cycling stability of lithium metal batteries. The as-obtained hybrid electrolytes exhibit improved mechanical and electrochemical properties enable the LiFePO4 /Li batteries to successfully cycling at a long time. fx1